The Significance of the Qur’anic Term and its Uses in Hashiyat al-Shihab al-Khafaji on al-Baydawi’s Interpretation - Rannah, Muhannad (Journal of Arabic Language Studies and Teaching, 2023)
The research seeks to prove the importance of language in understanding the meaning of speech, especially the Qur’anic meanings, and the interest of interpreters in Arabic methods and their derivations and the statement of meanings from the Qur’anic term, by revealing the contribution of Al-Shihab Al-Khafaji in this field in his footnote to Al-Baydawi’s Interpretation, since the features of Interpretation were distinguished after him as a multifaceted and varied science. Stripes, the language in these interpretations is highly tabulated; Al-Shihab Al-Khafaji was not an innovation when he made language one of the essential tools in his entourage and expanded on it. Intending to clarify and clarify the meaning, and accordingly; This research investigates, through a descriptive and analytical approach, the efforts of Al-Shihab Al-Khafaji and his approach to verify the signature of the Qur'anic term in his footnote to Al-Baydawi's Interpretation, which is marked "The Integrity of the Judge and the Sufficiency of the Radi". The research concluded that language is an indispensable tool in its footnotes, a measure of comprehension, and a criterion of analysis. Based on the intended Quranic meaning, not abstract linguistic consideration, he was interested in the significance of the Qur’anic term, defining the linguistic origins of the terminology, its derivations, and knowing the different uses of it, which helps to reveal the Qur’anic connotations, clarify their faces, and follow their goals.